Multiple primary carcinomas of the gastrointestinal tract. - Naaeder, S. B.; Jumah, K.B. (My University, 1998)
A case of multiple primary Carcinomas of the gastrointestinal tract is reported in a man presenting with Carcinomas of the rectum and oesophagus.
Keywords: EMTREE medical terms: adenocarcinoma; article; biopsy; case report; esophagus tumor; fatality; human; male; middle aged; multiple cancer; rectum tumor; squamous cell carcinoma MeSH: Adenocarcinoma, Papillary; Barium Sulfate; Biopsy; Carcinoma, Squamous Cell; Enema; Esophageal Neoplasms; Fatal Outcome; Humans; Male; Middle Aged; Neoplasms, Multiple Primary; Rectal Neoplasms